2012
DOI: 10.1111/j.1752-1688.2012.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioretention Design for Xeric Climates Based on Ecological Principles1

Abstract: Bioretention as sustainable urban stormwater management has gathered much recent attention, and implementation is expanding in mesic locations that receive more than 1,000 mm of annual precipitation. The arid southwestern United States is the fastest growing and most urbanized region in the country. Consequently, there is a need to establish design recommendations for bioretention to control stormwater from expanding urban development in this ecologically sensitive region. Therefore, we review the ecological l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Bureau of Reclamation, 2007) and therefore, does not meet LID objectives. Houdeshel et al, 2012). The control cell and upland cell included the infiltration bay shown in the image, however, the Wetland Cell did not.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Bureau of Reclamation, 2007) and therefore, does not meet LID objectives. Houdeshel et al, 2012). The control cell and upland cell included the infiltration bay shown in the image, however, the Wetland Cell did not.…”
Section: Introductionmentioning
confidence: 92%
“…These guidelines include: (1) the use of regionally native upland vegetation adapted to water-limited climates instead of wetland vegetation that has substantially higher water demands, and (2) routing stormwater to a sub-grade gravel storage layer instead of allowing stormwater to pond on the surface of bioretention facilities. Houdeshel et al (2012) demonstrated the hydrological performance of their suggested design, but the nutrient treatment performance of using upland vegetation in bioretention in concert with a sub-grade storage reservoir has not been tested.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The wetted perimeter (W p ) and hydraulic radius (r) were calculated applying Equations (15) and (16).…”
Section: Design Of the Infiltration Trenchmentioning
confidence: 99%